Construction of genetic linkage map and identification of QTLs related to agronomic traits in DH population of maize (Zea mays L.) using SSR markers - Choi, Jae-Keun; Sa, Kyu Jin; Park, Dae Hyun; Lim, Su Eun; Ryu, Si-Hwan; Park, Jong Yeol; Park, Ki Jin; Rhee, Hae-Ik; Lee, Mijeong; Lee, Ju Kyong (Genes & genomics, 2019)
Background In this study, we used phenotypic and genetic analysis to investigate Double haploid (DH) lines derived from normal corn parents (HF1 and 11S6169). DH technology offers an array of advantages in maize genetics and breeding as follows: first, it significantly shortens the breeding cycle by development of completely homozygous lines in two or three generations; and second, it simplifies logistics, including requiring less time, labor, and financial resources for developing new DH lines compared with the conventional RIL population development process. Objectives In our study, we constructed a maize genetic linkage map using SSR markers and a DH population derived from a cross of normal corn (HF1) and normal corn (11S6169). Methods The DH population used in this study was developed by the following methods: we crossed normal corn (HF1) and normal corn (11S6169), which are parent lines of a normal corn cultivar, in 2014; and the next year, the F 1 hybrids were crossed with a tropicalized haploid inducer line (TAIL), which is homozygous for the dominant marker gene R1 - nj (Nanda and Chase in Crop Sci 6:213–215, 1966 ), and we harvested seeds of the haploid lines. Results A total of 200 SSR markers were assigned to 10 linkage groups that spanned 1145.4 cM with an average genetic distance between markers of 5.7 cM. 68 SSR markers showed Mendelian segregation ratios in the DH population at a 5% significance threshold. A total of 15 quantitative trait loci (QTLs) for plant height (PH), ear height (EH), ear height ratio (ER), leaf length (LL), ear length (EL), set ear length (SEL), set ear ratio (SER), ear width (EW), 100 kernel weight (100 KW), and cob color (CC) were found in the 121 lines in the DH population. Conclusion The results of this study may help to improve the detection and characterization of agronomic traits and provide great opportunities for maize breeders and researchers using a DH population in maize breeding programs.